Avaliação dos aspectos sanitários, agronomicos e de qualidade em melancias irrigadas com esgoto tratado - Costa, Mayara Carantino (2006)
The reuse of treated sewage on watermelon irrigation, variety Crimson Sweet, was investigated not only considering the sanitary aspects but also the productivity and final product quality. The experiment was conducted in the Research Centre on Wastewater Treatment and Reuse, owned by the Company of Water and Wastewater of Ceará, in Aquiraz-CE. The experimental delimitation was randomized blocks, with four repetitions and four treatments: raw water and soil fertilization (T1); treated wastewater and soil fertilization (T2); treated wastewater without external soil fertilization (T3); and treated wastewater and half of soil fertilization (T4). The irrigation waters used (raw water and effluent of a stabilization pond) were characterized by the physical-chemical and microbiological aspects. Both waters were in the limits normalized by the World Health Organization (WHO) for unrestricted irrigation. The irrigation methods drip and furrow were compared in verifying of which one is more suitable for effluent reuse on watermelon production. The productivity data indicated that there was no significative difference among the treatments on drip irrigation, where the biggest productivities were obtained on T1 and T2 treatments. For the furrow system, no satisfactory productivity was achieved. The study revealed a significative difference among the treatments regarding the physical-chemical characteristics of the fruits. However, the microbiological quality was never compromised. Sensorial tests revealed that only the treatment T2 (treated wastewater and soil fertilization) did not present a different flavour, significative on 5% level, compared to the treatment T1 (control), and that the irrigation systems drip and furrow could be indifferently used without compromising the product flavour.